A Review of Teachers’ Awareness and Perceptions of Integrating the Flipped Classroom Model into Higher Education - Dawadi, Min Prasad; Panta, Prabhas; Shukla, Ajay Kumar (BIC Journal of Management, 2025)
The landscape of higher education is undergoing a significant transition in recent years as traditional, teacher-centered pedagogies give way to more student-centered teaching and learning strategies. Among the emerging pedagogical models, the flipped classroom model (FCM) has drawn considerable attention from the stakeholders for its potential to enhance student engagement and improve learning outcomes. This review paper examined fifty-five empirical studies published in high-ranked journals (Q1, Q2, Q3) between 2011 and 2025, focusing on the integration of FCM into regular teaching-learning practices in higher education. It explored the key factors associated with teachers’ awareness of the FCM, their perceptions of its effectiveness, and obstacles to its effective adoption. Additionally, it identified ways to overcome these barriers and effectively implement the model. The findings of the study revealed that while an increased awareness of the flipped class approach has been observed, teachers’ levels of preparedness and confidence in its implementation continue to remain low. While its ability to accommodate interactive and student-centered learning remains widely recognized, challenges such as time, technological, and resource limitations persist. These obstacles can be addressed through targeted training, institutional support, professional development opportunities, and a shared institutional vision.